2018
DOI: 10.3390/su10061750
|View full text |Cite
|
Sign up to set email alerts
|

A Functionality Based Wood Substitutability Index

Abstract: Recent progress in Life Cycle Impact Assessment highlighted the need to assess the loss of resources' functional value when assessing the life cycle impacts of resource depletion. To be able to assess the loss of functional value of resources due to scarcity and depletion, there is a need to assess the potential substitutions among different resources to fulfill the same functionality. In this sense, the main objective of this study is the development of a method for obtaining a substitution index (SI) for woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…As a natural resource, wood has the characteristics of lightweight and high strength and is rich in natural color and pattern [ 1 , 2 , 3 ]. It is widely used in the manufacture of furniture and other daily necessities [ 4 ]. Although wood is a renewable resource, its growth cycle is slow, and the wood itself has defects such as wet expansion and dry shrinkage, easy cracking, easy decay, and unstable size [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a natural resource, wood has the characteristics of lightweight and high strength and is rich in natural color and pattern [ 1 , 2 , 3 ]. It is widely used in the manufacture of furniture and other daily necessities [ 4 ]. Although wood is a renewable resource, its growth cycle is slow, and the wood itself has defects such as wet expansion and dry shrinkage, easy cracking, easy decay, and unstable size [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, maintenance activity, control of the building elements, replacement of parts are necessary to have the correct use of wood in construction... Many studies are moving in this direction, also in order to lenghten the life cycle of the materials used in the construction processes [4]. A Recent study has demonstrated the relevance of green supply chain [5,6] and sustainable waste management [7] confirming the importance of promoting recycling and renewable policies [8].…”
Section: Introductionmentioning
confidence: 99%